Promising novel therapeutic approaches in the management of gastrointestinal stromal tumors. (January 2017) - Szucs, Zoltan; Thway, Khin; Fisher, Cyril; Bulusu, Ramesh; Constantinidou, Anastasia; Benson, Charlotte; van der Graaf, Winette TA; Jones, Robin L
Primary and secondary resistance to currently available licensed tyrosine kinase inhibitors poses a real clinical challenge in the management of advanced gastrointestinal stromal tumors. Within the frame of early phase clinical trials novel systemic treatments are currently being evaluated to target both the well explored and novel emerging downstream effectors of KIT and PDGFRA signaling. Alternative therapeutic approaches also include exploring novel inhibitors of the KIT/PDGFRA receptors, immune checkpoint and cyclin-dependent kinase inhibitors. The final clinical trial outcome data for these agents are highly anticipated. Integration of new diagnostic techniques into routine clinical practice can potentially guide tailored delivery of agents in the treatment of a highly polyclonal, heterogeneous disease such as heavily pretreated advanced gastrointestinal stromal tumor.